Improving The UI/UX Quality Of The JasBi Application Using UEQ And UCD - Talasari, Resky Ayu Dewi; Ilham, Karina Fitriwulandari; Yuhana, Umi Laili (PINISI Discretion Review, 2024)
This research was conducted to analyze and evaluate the User Interface (UI) and User Experience (UX) contained in the JasBi application using a User Experience Questionnaire (UEQ) and User Centered Design (UCD). At the first questionnaire distribution stage, JasBi application users were less satisfied with the existing UI. This research is a quantitative study using a survey method of those who use the JasBi application. Based on the design of solutions using the UCD method results in the following results: interest in the JasBi application UI is excellent (value 2.30), clarity in the JasBi application (averaged 1.98), efficiency in the JasBi application is excellent (value 2.30), simulation in the JasBi application is excellent (averaged 1.88), newness in the JasBi application (2.10).